The Effect of Student Worksheets Through the Edmodo Network on Concept Understanding and Independent Learning on Hydrocarbon Materials - Khairini Khairini; Ibnu Khaldun; Andi Ulfa Tenri Pada (Postgraduate, University of Mataram, 2021)
This study aims to determine the effect of student worksheets through the Edmodo network on understanding concepts and learning independence on hydrocarbon material. The research method used is an experiment with a quantitative approach. The research design used was a pretest-posttest control group design. The population of this study was students of class XI SMAN 5 Banda Aceh with data collection techniques by random sampling to obtain two classes that became the research sample. The research instruments used were reasoned test questions and questionnaires. Based on the results of the t-test analysis of conceptual understanding with a significant score of 0.015 <0.05, it shows that there is a significant difference between the control class and the experimental class. The results of the t-test of students' learning independence showed that the significant score was 0.000 <0.05, which means that the data had a significant difference between the control and experimental classes. The conclusion in this study is that student worksheets through the Edmodo network can affect students' understanding of concepts and learning independence. This research concludes that using student worksheets through the Edmodo network in chemistry learning is more effective in increasing understanding of concepts and students' learning independence for the better